Cutaneous involvement in multiple myeloma. A rare entity - L. Rapparini; A. Pileri; S. Robuffo; C. Agostinelli; Michelangelo La Placa (Clinical Case Reports)
Key Clinical Message Cutaneous involvement in multiple myeloma is rare and may present as nodules mimicking other lymphoid neoplasms. It typically occurs late in the course of the disease and is associated with an aggressive clinical course and poor prognosis.